Unlocking the Potential of Women Farmers in Indonesia Through Digital Technology - Kenny Pradipta Montoya Putra Pratama; Ali Zainal Abidin; Cindy Putri Sukmawati; Trian Gigih Kuncoro (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Women play a strategic role in Indonesia’s agricultural sector; however, their contribution to productivity and economic development remains constrained by limited access to land, capital, information, and technology. Advances in digital technology offer significant opportunities to improve production efficiency, expand market access, and strengthen the economic empowerment of women farmers. Nevertheless, empirical and conceptual studies that specifically examine the adoption of digital technology by women farmers in Indonesia are still limited and fragmented. This study aims to comprehensively review the types of digital technologies adopted by women farmers in Indonesia, the factors influencing such adoption, and its impacts on productivity, income, and welfare. The study employs a qualitative approach through a systematic literature review of 70 reputable scientific articles published between 2011 and 2023, analyzed using content analysis techniques. The findings indicate that the use of mobile phones, digital extension services, e-commerce platforms, and smart agricultural technologies contributes positively to reducing information asymmetry, improving production efficiency, expanding market access, and strengthening the role of women farmers in decision-making. However, the adoption of digital technology remains constrained by low digital literacy, limited infrastructure, restricted access to capital, and gender-based social norms. The implications of this review underscore the importance of gender-responsive digital inclusion policies to promote rural economic growth, food security, and sustainable agricultural development.